Flow pattern evolution in natural convection cooling from an array of discrete heat sources in a rectangular cavity at various orientations - TSO, C (2004)
Experimental data are presented for laminar natural convection cooling of water in a rectangular cavity with a 3 x 3 array of heaters on one wall, and the cavity at various inclined angles. Generally, heaters in the same row have close temperatures, due to weak velocity in the horizontal direction. Numerical simulations in 2-D and 3-D are also reported, showing flow and temperature pattern evolution at different inclined angles. In particular, the case of horizontal cavity heated from below reveals flow fields of the toroidal, bimodal or Rayleigh-Benard convection type, depending on the Rayleigh number.. and this is also the most desirable orientation for heat transfer. When the enclosure is inclined toward the horizontal orientation (heated from below), the flow and temperature fields become complex and distorted. (C) 2004 Elsevier Ltd. All rights reserved.